Application of Project-Based Learning (PjBL) to Improve Critical Thinking Skills and Students' Learning Independence on the Making of Colloids in Dispersion - Desiana, Gita Annissa; Sulastri, Sulastri; Syahrial, Syahrial (JTK (Jurnal Tadris Kimiya), 2022)
Critical Thinking Skills (CTS) and student learning independence are two things related to the learning process. The low independence of student learning affects critical thinking skills in solving a learning problem. A project-based learning model can improve critical thinking skills and independent learning. This study aims to analyze the application of the PjBL model to manufacture colloids to improve students' critical thinking skills and independent learning at MAN 1 Banda Aceh. The type of research used is quasi experimental. The samples of this study were students of natural science two 11th grade as control class and students of natural science four 11th grade as experimental class, which had normal distribution and had the same variance. The instruments of this research are the CTS test questions and learning independence questionnaires. The results show that applying the PjBL model can improve critical thinking skills (CTS) with an average N-gain value in the medium category, then the CBC analysis of indicators is in the high category. The results of testing the CTS hypothesis for experimental class and control class students are also significantly different, meaning that the CTS model can improve students' critical thinking skills. The analysis of student learning independence results obtained an average score of N-gain, including the medium category. The results of the hypothesis test of student learning independence in the experimental and control classes are also significantly different, meaning that the PjBL model can increase learning independence. The results obtained prove that the PjBL model can improve CTS and learning independence better than in the control class.